Contribution of Epidural Injections in the Management of Radiculopathy by Lumbar Disc Herniation: A Narrative Review - Dawood Al-Jubouri , Muhanad; Saad Madhi , Zaid; Salman Al-Jubouri , Dawood; Ali Hasan , Mohannad (Hammurabi Journal of Medical Sciences, 2025)
Epidural injections considered to be the mostly performed nonsurgical treatment for radicular pain due to Lumbar disc herniation. Different types of epidural injections have been used in the management of lumbar radiculopathy including local anesthetics only, different types of steroids, and combined steroids and local anesthetics using different approaches.The objective of this review to examine the effectiveness of epidural injections in the management of sciatica. High quality evidence with different study design will be discussed including Systematic reviews, Randomised Control trials (RCTs) and retrospective studies. Different types of epidural injections have been studied in the management of lumbar radiculopathy including local anaesthetics only, different types of steroids, and combined steroids and local anaesthetics using different approaches. Studies have been conducted in order to assess the superiority of one type on the other in term of pain relief, functional improvement, and reduce the surgical intervention.The literature has shown that epidural injections are effective treatment for LDH in term of both pain relief and functional improvement regardless of the type of injections whether steroids with local anaesthetics or local anaesthetics alone. There is strong evidence showing that epidural injections are more effective in the short term (< 6 months) than the long term (> 6 months).